P01.042 Symptom clusters in newly diagnosed glioma patients: which clusters are associated with functioning and global health status?. (19th September 2018) - Coomans, M B; Dirven, L; van den Bent, M; Bottomley, A; Coens, C; Stupp, R; Weller, M; Reijneveld, J C; Taphoorn, M J B; ,
Abstract: Introduction: Symptom management in glioma patients remains a challenge, as patients suffer from various concurrent occurring symptoms. This study aimed to identify symptom clusters and to examine the relation between these symptom clusters and functioning. Methods: We prospectively included individual patient data from previously published international randomized controlled trials (RCTs) in glioma patients. Symptom prevalence and level of functioning were assessed with EORTC QLQ-C30 and QLQ-BN20 questionnaires. The magnitude of the associations between symptoms were examined with Spearman correlation coefficients and correlation matrices. Hierarchical cluster analyses (looking at euclidean distances) were performed to identify symptom clusters. Multivariable regression analyses were performed to analyze associations between the symptom clusters and functioning, adjusted for confounding variables. Results: Data of 3595 newly diagnosed glioma patients who completed the questionnaires before randomization indicated that many patients (44%) suffered from 5–10 symptoms simultaneously. The most prevalent symptoms were fatigue, drowsiness and motor dysfunction, experienced by 86%, 59% and 55% of the patients respectively. Five symptom clusters were identified with hierarchical cluster analyses: motor cluster, fatigue cluster, headache cluster, gastrointestinal/seizures cluster and hair loss/itchy skin cluster. Having symptoms in the motor cluster had a clinically relevant and significant negative influence (≥10points difference) on the global health status/quality of life scale, and physical, role, cognitive and social functioning (Beta's ranged from -10.9 to -18.6, all p<0.001). Similarly, having symptoms in the fatigue cluster had a clinically relevant negative influence on the global health status/quality of life scale, and role and social functioning (Beta's ranged from -10.7 to -15.5, all p<0.001) Conclusions: Two symptom clusters, the fatigue and motor cluster, were frequently affected in glioma patients and demonstrated to negatively influence functioning and global quality of life. Implementation of interventions targeting fatigue and motor problems would therefore contribute to improved functioning and quality of life in glioma patients.